Late Tertiary-Quaternary Geological Evolution of the Houtman Abrolhos Carbonate Platforms, Northern Perth Basin - Collins, Lindsay; Zhu, Z.; Wyrwoll, K. (Petroleum Exploration Society of Australia, 1998)
The Houtman Abrolhos coral reefs are three shelf-edge carbonate platforms which together form the discontinuously rimmed Abrolhos Shelf. During the Tertiary to Quaternary there was a vertical transition from cool-water ramp sedimentation to reefal platform development near the shelf edge, producing a discontinuously rimmed shelf during the Quaternary. The facies transition owes its existence to regional patterns of oceanographic circulation, driven in the longer term by plate tectonic and palaeolatitude changes, whilst changes in the frequency of sea level oscillations controlled a transition from late Tertiary third order cycles, to fourth and fifth order cycles during the Quaternary. Seismic investigations and coring have confirmed the existence of 4-6m thick, unconformity-bounded shelf sequences which are the lateral equivalents of reef' buildups within the platforms during the Quaternary.Reef limestones of Last Interglacial age are dense and calcretized, in marked contrast with the more porous Holocene lithofacies. Coral framestone facies of the Last Interglacial consist mainly of branching coral or head coral, with minor encrusting coralline algae and white lime mud. The exposed uppermost part of the Last Interglacial reefs of the central platforms normally consists of an upward-shallowing sequence, commonly 2-3m thick and locally up to 6m thick. In the 'large' islands of the Wallabi Group, aeolianites cap the sequence.Late Quaternary platform evolution has been influenced by sea level oscillations and differing wave energy regimes. Each of the three island groups in the Abrolhos consists of a central platform of Last Interglacial reefs, about which windward and leeward Holocene reefs have developed asymmetrically. Most Holocene reef growth took place on the lee-side of an antecedent platform from an essentially flat surface, generating Holocene constructional topography characterised by 'blue-hole' terrain, which was previously interpreted as karst. The Holocene sea level record provided by dates from the 40m thick leeward reef is the first such record from the western continental margin of Australia.The Abrolhos carbonate platforms provide new insights into the evolution of carbonate ramps to rimmed shelves on passive margins, cool- to warm-water carbonate facies transitions, and the interaction of sea level change, antecedent topography and wave energy regimes in platform evolution and facies architecture. An understanding of these geological processes is also vital for sound environmental management.